iCCell: Uma Abordagem Distribuída na Internet das Coisas para Contagem de Fibroblastos - Porto, Mateus Parker; Diniz, Cláudio Machado; Yamin, Adenauer Corrêa (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2022: Anais do XLIX Seminário Integrado de Software e Hardware, 2022)
Cell count is a process usually performed in clinical analysis laboratories, very significant for the diagnosis of different diseases. With this motivation, this work aims to design an approach, called iCCell, which integrates an embedded platform, responsible for the acquisition of images captured from microscopes and a computational cloud infrastructure, responsible for both the counting of cells in these images, the storage, as well as the entire user interface. The iCCell was evaluated using images produced by the Clinical Neurosciences Laboratory of the Catholic University of Pelotas (UCPel). The results achieved so far are promising and point to the continuity of research.